Modifier, cement crushed stone mixture, and preparation method
By using modifiers in cement gravel mixture, we work together to reduce water, retain water, sustain release, compactness, toughening and anti-cracking, and solve the crack problems caused by temperature and dry shrinkage of the water stabilized layer, which significantly improves the cracks. The crack resistance of cement stabilizes the material extends the service life of the road surface.
Patent Information
- Application Number
- CN202310345964.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The water-stabilizing layer produces cracks during the temperature shrinkage and dry shrinkage, resulting in reduced pavement strength and insufficient load-bearing capacity, affecting its performance and durability. It is especially serious in areas with large temperature difference and strong wind, resulting in a shortening of the pavement service life.
A modifier is provided, including methallyl alcohol polyoxyethylene ether, methacrylic acid, cellulose, nanoSiO2, polyacrylate emulsion, propylene glycol and silicone-polyvinyl alcohol nanocomposite hydrogel, by reducing water , water retention, sustained release, compaction, toughening, and crack resistance, synergistically acts to prepare cement gravel mixtures and improve the crack resistance of the water stabilizer layer.
It significantly improves the crack resistance of the water-stabilizing layer, reduces the occurrence of reflective cracks, extends the service life of the road surface, and forms a stable network structure, which improves the toughness and deformation ability of cement stabilized materials.
Smart Images

Figure GDA0004936112600000081 
Figure GDA0004936112600000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to a modifier, a cement crushed stone mixture and a preparation method. Background Art
[0002] As the main form of semi-rigid base, stabilized mixture is widely used in highway construction. Since the cementitious material in the water-stabilizing layer has shrinkage characteristics, it is inevitable that cracks will occur due to temperature shrinkage and dry shrinkage, especially in areas with large temperature differences and strong winds, which will lead to the overall strength of the water-stabilizing layer being reduced and the local bearing capacity being insufficient, resulting in the formation of reflective cracks. The cracks seriously affect the performance of the road surface, reduce durability, and significantly reduce the service life of the road surface. Summary of the invention
[0003] <Technical Problems Solved by the Invention>
[0004] The invention is used to solve the problem in the prior art that the shrinkage of the water-stabilizing layer causes cracking, thereby shortening the service life of the road surface.
[0005] <Technical solution adopted by the present invention>
[0006] In view of the above technical problems, the object of the present invention is to provide a modifier, a cement crushed stone mixture and a preparation method.
[0007] The modifier provided by the present invention can greatly improve the anti-cracking ability of the water-stabilizing layer through the synergistic effect of components with functions such as water reduction, water retention, slow release, densification, toughening, and crack resistance, greatly alleviate the problem of reflective cracks in the water-stabilizing layer, and further extend the service life of the road surface.
[0008] The specific contents are as follows:
[0009] First, the present invention provides a modifier, wherein each component, by weight percentage, comprises
[0010] Methyl allyl alcohol polyoxyethylene ether 10%-30%, methacrylic acid 8%-25%, cellulose 8%-20%, nano-SiO2 1%-1.8%, polyacrylate emulsion 30%-65%, propylene glycol 0.5%-3%, silicone-polyvinyl alcohol nanocomposite hydrogel 3%-8%.
[0011] Second, the present invention provides a method for preparing the aforementioned modifier, comprising the following steps:
[0012] S1: After heating the polyacrylate emulsion, methyl allyl alcohol polyoxyethylene ether, methacrylic acid and nano-SiO2 are added and blended to obtain a first blend;
[0013] S2: adding cellulose and organosilicon-polyvinyl alcohol nanocomposite hydrogel to the first blend to obtain a second blend;
[0014] S3: adding propylene glycol to the third blend to obtain a modifier.
[0015] Third, the present invention provides a cement-gravel mixture, wherein the components, by weight percentage, include 20% to 30% of 0-5mm machine-made sand, 20% to 30% of 5-10mm gravel, 10% to 30% of 10-15mm gravel, 10% to 25% of 15-20mm gravel, 10% to 30% of 20-25mm gravel, 0.8% to 1.5% of the aforementioned modifier, 2% to 5% of cement, and the balance is water.
[0016] Fourthly, the present invention provides a method for preparing the cement crushed stone mixture mentioned above,
[0017] S1: Evenly mix 0-5 mm machine-made sand, 5-10 mm crushed stone, 10-15 mm crushed stone, 15-20 mm crushed stone, 20-25 mm crushed stone and cement to obtain a crushed stone mixture;
[0018] The S2 modifier is mixed with water to obtain an additive liquid;
[0019] S3: adding the additive liquid to the gravel mixture while stirring to obtain a cement gravel mixture.
[0020] <Beneficial Effects of the Invention>
[0021] The modifier provided by the present invention has the effects of super toughness and crack resistance. By utilizing its effects of water reduction, water retention, slow release, compaction, toughening and crack resistance, it can form a stable network structure in the water-stabilized mixture, and then form a cement stabilizer with less shrinkage, high toughness and large deformation ability, which can greatly improve the crack resistance of the water-stabilized layer, and then greatly alleviate the problem of reflective cracks in the water-stabilized layer, thereby extending the service life of the pavement. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0023] <Technical solution>
[0024] First, the present invention provides a modifier, wherein each component, by weight percentage, comprises
[0025] Methyl allyl alcohol polyoxyethylene ether 10%-30%, methacrylic acid 8%-25%, cellulose 8%-20%, nano-SiO2 1%-1.8%, polyacrylate emulsion 30%-65%, propylene glycol 0.5%-3%, silicone-polyvinyl alcohol nanocomposite hydrogel 3%-8%.
[0026] Furthermore, each component, by weight percentage, includes
[0027] Methyl allyl alcohol polyoxyethylene ether 12%-28%, methacrylic acid 10%-20%, cellulose 0.8%-1.5%, nano-SiO2 1%-1.5%, polyacrylate emulsion 35%-60%, propylene glycol 0.5%-2.5%, silicone-polyvinyl alcohol nanocomposite hydrogel 4%-6%.
[0028] Furthermore, the organosilicon-polyvinyl alcohol nanocomposite hydrogel is an existing technology, and the specific preparation method is: polyvinyl alcohol, silane coupling agent hydrolyzate, ethanol, and deionized water are blended, heated to 85°C, and stirred for 5 to 6 hours to obtain a blended liquid; the blended liquid is then cooled, poured into a mold, and subjected to a cycle of freezing-thawing, and then soaked in deionized water to obtain a finished product. The mass ratio of polyvinyl alcohol, silane coupling agent, ethanol, and deionized water is 15:2.5:15:70. The silane coupling agent is KH550, and in the silane coupling agent hydrolyzate, polyvinyl alcohol accounts for 80% and deionized water accounts for 20%.
[0029] Second, the present invention provides a method for preparing the aforementioned modifier, comprising the following steps:
[0030] S1: After heating the polyacrylate emulsion, methyl allyl alcohol polyoxyethylene ether, methacrylic acid and nano-SiO2 are added and blended to obtain a first blend;
[0031] S2: adding cellulose and organosilicon-polyvinyl alcohol nanocomposite hydrogel to the first blend to obtain a second blend;
[0032] S3: adding propylene glycol to the third blend to obtain a modifier.
[0033] Furthermore, in S1, the temperature is heated to 15°C to 25°C.
[0034] Furthermore, in S2, the blending temperature is 20°C to 40°C.
[0035] The modifier provided by the invention is a stable emulsion material.
[0036] Third, the present invention provides a cement-gravel mixture, wherein the components, by weight percentage, include 20% to 30% of 0-5mm machine-made sand, 20% to 30% of 5-10mm gravel, 10% to 30% of 10-15mm gravel, 10% to 25% of 15-20mm gravel, 10% to 30% of 20-25mm gravel, 0.8% to 1.5% of the aforementioned modifier, 2% to 5% of cement, and the balance is water.
[0037] Furthermore, the components, by weight percentage, include 22% to 28% of 0-5mm machine-made sand, 22% to 28% of 5-10mm crushed stone, 12% to 28% of 10-15mm crushed stone, 12% to 20% of 15-20mm crushed stone, 12% to 28% of 20-25mm crushed stone, 0.8% to 1.2% of modifier, 2% to 5% of cement, and the balance is water.
[0038] Fourthly, the present invention provides a method for preparing the aforementioned cement crushed stone mixture, comprising the following steps:
[0039] S1: Evenly mix 0-5 mm machine-made sand, 5-10 mm crushed stone, 10-15 mm crushed stone, 15-20 mm crushed stone, 20-25 mm crushed stone and cement to obtain a crushed stone mixture;
[0040] The S2 modifier is mixed with water to obtain an additive liquid;
[0041] S3: adding the additive liquid to the gravel mixture while stirring to obtain a cement gravel mixture.
[0042] The present invention firstly stirs the modifier and water evenly to prepare an emulsion, then adds it to the crushed stone, machine-made sand and cement mixture, and then stirs while adding the modifier emulsion, and mixes evenly after adding to obtain an ultra-tough anti-cracking cement-stabilized crushed stone mixture. This method can ensure that various materials are evenly dispersed, thereby improving the polymerization strength between the materials, and can be better used for water-stable base mixtures.
[0043] The modifier provided by the present invention is used as an admixture to improve the road performance of water-stabilized mixture.
[0044] The standard range of cement dosage in cement-stabilized crushed stone mixture is 2-6%.
[0045] The dosage of the modifier is 0.8-15% of the mass of the cementitious material.
[0046] <Example>
[0047] Example 1
[0048] An ultra-tough crack-resistant cement-stabilized crushed stone mixture, weighing the following components:
[0049] 92kg cement; 850kg 0-5mm fine aggregate; 814kg 5-10mm coarse aggregate; 408kg 10-20mm coarse aggregate; 183kg 20-25mm coarse aggregate; 119kg water (standard value), the actual water consumption is reduced by about 25% to 89kg, and 0.9kg modifier (1% of cement mass). Coarse aggregate is crushed stone.
[0050] Specifically, the cement dosage is 4%, the maximum dry density is 2.340, the optimal moisture content is 5%, and the compaction degree is not considered.
[0051] Specifically, the water storage tank capacity is: 50 tons, and the construction volume on the day is: 500m 3 The total water consumption is 44 tons, the total rubber consumption is 45 tons, and the total modifier consumption is 450 kg.
[0052] Specifically, the modifier includes the following components: 110 kg of methyl allyl alcohol polyoxyethylene ether, 115 kg of methacrylic acid, 40 kg of cellulose, 6 kg of nano-SiO2 polymer material, 195 kg of polyacrylate emulsion, 4 kg of propylene glycol, and 25 kg of silicone-polyvinyl alcohol nanocomposite hydrogel; 450 kg of the prepared modifier is added to 44 tons of water.
[0053] The preparation method of the modifier is as follows: after heating 195kg of polyacrylate emulsion to 15°C to 25°C, 110kg of methyl allyl alcohol polyoxyethylene ether, 115kg of methacrylic acid, and 6kg of nano-SiO2 polymer material are added and stirred evenly for 15 minutes; then 40kg of cellulose and 25kg of silicone-polyvinyl alcohol nano-composite hydrogel are added and stirred at 20°C to 40°C for 10 minutes, and finally 4kg of propylene glycol is added and stirred for 5 minutes to prepare the modifier.
[0054] Specifically, 44 tons of water are weighed in advance and stored in a water tank (tank), and then 450 kg of modifier is added into the water tank (tank) and stirred evenly to form a mixed liquid. During the production process, the modifier mixed solution tank is continuously stirred; and then production is carried out according to the steps of the production process.
[0055] Specifically, the production of water-stabilized mixture adopts a two-time mixing method, and the time of the two mixings can be maintained at more than 10 seconds so that the modifier mixed solution can be mixed with the dry mixed material as fully and evenly as possible.
[0056] Specifically, after the mixture is produced, it should be covered with felt cloth in time to prevent water evaporation. Because the modifier has a certain water retention function, it can extend the working performance of the water-stabilized mixture by about 1 hour, which is conducive to long-distance transportation.
[0057] Specifically, the mixture spreading, rolling, curing, traffic control and interlayer treatment shall be carried out in accordance with the provisions of "JTGTF20-2015 Technical Specifications for Highway Pavement Base Construction".
[0058] The preparation method of cement stabilized crushed stone mixture is as follows: firstly, cement, 0-5mm fine aggregate, 5-10mm coarse aggregate, 10-20mm coarse aggregate and 20-25mm coarse aggregate are transported into a mixer, a modifier mixed solution is added, and the mixture is evenly mixed by secondary stirring to obtain a cement stabilized crushed stone mixture.
[0059] Example 2
[0060] The difference between this embodiment and embodiment 1 is that:
[0061] The components of the modifier are: 100kg of methyl allyl alcohol polyoxyethylene ether, 90kg of methacrylic acid, 45kg of cellulose, 5kg of nano-SiO2 polymer material, 205kg of polyacrylate emulsion, 6kg of propylene glycol, and 22kg of organic silicon-polyvinyl alcohol nano-composite hydrogel.
[0062] <Test example>
[0063] Test Example 1
[0064] The properties of the modifier prepared in Example 1 were measured, and the results are shown in Table 1.
[0065] Table 1 Properties of modifiers
[0066] project unit index Test methods density g / L ≧1.05 GBT 8077 Solid content % ≧25 GBT 8077 pH / ≧4.5 GBT 8077 Alkali content mg / L ≤150 GBT 8077 SO42- content mg / L ≤270 GBT 8077 Cl- content mg / L ≤350 GBT 8077
[0067] Test Example 2
[0068] The compaction test and 7-day unconfined compressive strength test results are used as the basis for engineering inspection, quality control and evaluation during the construction process.
[0069] Specifically,
[0070] (1) The 7-day unconfined compressive strength is used as the main indicator for the construction quality control of inorganic binder stabilized materials. In order to improve the quality of the project and reduce the risk and probability of cracking of the semi-rigid base, new technical requirements are proposed for cement-stabilized crushed stone mixtures with modifiers, mainly including: splitting strength, flexural strength, static compressive rebound modulus, fatigue, freeze-thaw, temperature shrinkage deformation, and dry shrinkage deformation.
[0071] (2) Specific technical indicators of cement-stabilized crushed stone mixture with modifier added are shown in Table 2.
[0072] (3) The new technical requirements for cement-stabilized crushed stone mixture with added modifiers are as follows:
[0073] ① The splitting strength should not be less than 0.45MPa;
[0074] ② The bending tensile strength should not be less than 0.90MPa;
[0075] ③ All test data of other indicators are collected to form a database of cement-stabilized crushed stone material system, which is the basis for the scientific development and application of water-stabilized materials. At the same time, through a large amount of data collection, collation, and scientific and rigorous mathematical model analysis, it is helpful to improve the comprehensive performance of water-stabilized material construction.
[0076] The properties of the cement-stabilized crushed stone mixture prepared in Example 1 are shown in Table 3.
[0077]
[0078]
[0079] It can be seen from the data in Table 3 that after the modifier is added to the water-stabilized mixture in the present invention, the obtained cement-stabilized gravel mixture has excellent performance, less hardening shrinkage, small rigidity, strong deformation resistance, and is safe and durable. It can be better used for semi-rigid base mixture to resist cracking, reduce the cracking of the semi-rigid base water-stabilized layer pavement, improve the toughness of the water-stabilized base, increase the earlier generation of reflective cracks in the pavement, and extend the service life of the pavement.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modifier, characterized in that: The components are calculated by weight percentage, including Methyl allyl alcohol polyoxyethylene ether 10%-30%, methacrylic acid 8%-25%, cellulose 8%-20%, nano-SiO2 1%-1.8%, polyacrylate emulsion 30%-65%, propylene glycol 0.5%-3%, silicone-polyvinyl alcohol nanocomposite hydrogel 3%-8%.
2. The modifier according to claim 1, characterized in that The components are calculated by weight percentage, including Methyl allyl alcohol polyoxyethylene ether 12%-28%, methacrylic acid 10%-20%, cellulose 8%-15%, nano-SiO2 1%-1.5%, polyacrylate emulsion 35%-60%, propylene glycol 0.5%-2.5%, silicone-polyvinyl alcohol nanocomposite hydrogel 4%-6%.
3. The method for preparing a modifier according to any one of claims 1 to 2, characterized in that: The steps include: S1: After heating the polyacrylate emulsion, methyl allyl alcohol polyoxyethylene ether, methacrylic acid and nano-SiO2 are added and blended to obtain a first blend; S2: adding cellulose and organosilicon-polyvinyl alcohol nanocomposite hydrogel to the first blend to obtain a second blend; S3: adding propylene glycol to the third blend to obtain a modifier.
4. The method for preparing the modifying agent according to claim 3, characterized in that: In S1, the temperature is heated to 15°C to 25°C.
5. The method for preparing the modifying agent according to claim 3 or 4, characterized in that: In S2, the blending temperature is 20°C to 40°C.
6. A cement crushed stone mixture, characterized in that: The components, measured by weight percentage, include 20% to 30% of 0-5mm machine-made sand, 20% to 30% of 5-10mm crushed stone, 10% to 30% of 10-15mm crushed stone, 10% to 25% of 15-20mm crushed stone, 10% to 30% of 20-25mm crushed stone, 0.8% to 1.5% of the modifier as claimed in any one of claims 1 to 2 or the modifier obtained by the preparation method of any one of claims 3 to 5, 2% to 5% of cement, and the balance is water.
7. The cement crushed stone mixture according to claim 6, characterized in that: The components, by weight percentage, include 22% to 28% of 0-5mm machine-made sand, 22% to 28% of 5-10mm crushed stone, 12% to 28% of 10-15mm crushed stone, 12% to 20% of 15-20mm crushed stone, 12% to 28% of 20-25mm crushed stone, 0.8% to 1.2% of modifier, 2% to 5% of cement, and the balance is water.
8. A method for preparing a cement crushed stone mixture as claimed in claim 6 or 7, characterized in that: The steps include: S1: Evenly mix 0-5 mm machine-made sand, 5-10 mm crushed stone, 10-15 mm crushed stone, 15-20 mm crushed stone, 20-25 mm crushed stone and cement to obtain a crushed stone mixture; The S2 modifier is mixed with water to obtain an additive liquid; S3: adding the additive liquid to the gravel mixture while stirring to obtain a cement gravel mixture.
Citation Information
Patent Citations
Water-based polyacrylate emulsion and preparation method thereof
CN106832106A
Cement stabilized macadam
CN107445560A
Construction method of stabilized macadam self-curing cement layer pavement
CN113233814A
Cement stabilized macadam base composition and preparation and construction process thereof
CN114180896A
